(untitled) (Revista Contexto & Saúde, 2024)
HPV is the etiological agent of cervical cancer. It is the second leading neoplasm among women, when less developed and low-income countries are considered. Despite the development of three vaccines that are effective in preventing HPV-related infections and lesions, complete compliance with the vaccination schedule is not always observed. It is believed that the number of doses may be a major factor in low adherence. To this end, the objective of the study was to verify whether the reduced dose schedule has comparable efficacy and durability to the expanded schedule. This is a matter of systematic literature review whose bibliographic research strategy included consultation of the PubMed and SciELO research bases in the first half of 2022. The inclusion criteria were randomized clinical studies published in English, Portuguese, or Spanish; Publications from the last five years; Publications in which the intervention is the application of the vaccine to the adolescent or adult population; Publications that evaluate different vaccination schedules and Publications with an outcome related to the effectiveness and durability of vaccination schedules. The criteria were assessed by two independent reviewers and the risk of bias in the publications was analyzed using the CONSORT checklist. 54 articles were gathered, of which 12 were eligible. The results of this study showed that reduced regimens of one or two doses have satisfactory immunogenicity, efficacy, and durability of anti-HPV protection, without any disadvantages in relation to three-dose regimens. Therefore, reduced schedules become an immunization strategy, especially with regard to developing countries, which would have their vaccination programs strengthened and vaccination coverage expanded